Physics Teachers' Ability to Reflect on Learning: A Case Study in Palu City - Nurjannah Nurjannah; Supriyatman Supriyatman; Amiruddin Kade (Equator Science Journal, 2026)
This study aims to map the learning-reflection ability of Physics teachers in Palu City, Central Sulawesi, at both the planning and implementation levels, and to analyse the influence of Guru Penggerak (Teacher-Mover) status on the quality of reflection displayed. The study employs a qualitative approach with a multiple case study design involving seven Physics teachers from seven public senior high schools, purposively selected on the principle of maximum variation. Data were collected through document analysis of lesson plans (RPP/Teaching Modules), 21 non-participant classroom observations, and triangulation interviews with 21 students. The main instrument was a review-and-observation sheet based on twenty reflection indicators synthesised from the frameworks of Schön, Hatton and Smith, and the revised Bloom taxonomy. The results show that the average reflection ability of the teachers reached only 19% at the planning stage and 21% at the implementation stage, both of which fall within the very low category according to the Larrivee framework. Reflection questions were dominated by ritualistic closed formats at the descriptive-writing level, with four metacognitive indicators not appearing at all across the participants. Guru Penggerak teachers consistently displayed higher reflective capacity (28%) than regular teachers (18%), particularly in the closing stage of the lesson. These findings indicate that academic qualifications and long teaching experience are not automatically correlated with reflective ability, and underscore the importance of developing a standardised reflection toolkit based on Social Emotional Competence to support the implementation of the Kurikulum Merdeka.